The Influence of Social Media Advertising and Content Quality on Consumer Behavior in Digital Business - Syafiq, Raki Khoery; Haris, Ibnu; Taryono (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Particularly in the context of digital business, the advancement of information and communication technology has had a profound impact on consumer behavior.  In order to better understand how social media advertising and content quality impact consumer behavior, this study will be analyzing just that.  Quantitative methods with a descriptive approach are utilized in the investigation.  A hundred people who are well-versed in digital transactions and who regularly use social media were polled online. Validity and reliability tests, testing of the classical assumptions, and multiple linear regression analysis were used to analyze the data.  According to the findings, social media advertising and content quality both have a favorable and substantial impact on consumer behavior. The two variables account for 71.5% of the variance in consumer behavior, according to the coefficient of determination value of 0.715. This study provides practical contributions for digital business practitioners in improving the effectiveness of marketing strategies through optimized advertising and high-quality content delivery on social media.